AB1349 The effect of biological therapy on work participation in ankylosing spondylitis patients: A systematic review. (23rd January 2014) - van der Burg, L.; ter Wee, M.; Boonen, A.
Abstract : Background: In the pre-biologics era several studies showed a large impact of ankylosing spondylitis (AS) on worker participation.[1] Biologicals offer the opportunity to improve work-outcomes on the one hand and offset part of the drug costs on the other hand. Objectives: To systematically review the effect of treatment with biologicals in AS on three areas of work-outcomes: employment status, absence form paid work and at-work productivity loss. Methods: A systematic search in Pubmed, Embase and Cochrane Library was performed (15 June 2011) by two authors to identify relevant articles. Quality of included studies was assessed by two authors using the Dutch Cochrane guidelines for (un)controlled cohorts and randomised controlled trials (RCTs). Data were extracted by one author (LvdB) and checked by another (MtW) using a self-composed form. Due to extensive inter-study heterogeneity, narrative summaries were used to present the data. Results: A total of eight studies were included (5 uncontrolled cohorts, 1 population controlled cohort and 2 RCTs) and 26 comparisons of either before-after TNF or between treatment groups were reported. Overall 877 patients were treated with three different TNF-α inhibitors (etanercept, infliximab, adalimumab). While the methodological quality of RCTs was good, they lack external validity. Of the five cohort studies, three showed substantial selection bias and three did not control outcomes for potential confounders. Although trends for all outcomes were positive, only 7 of 13 before-after comparisons in the five uncontrolled cohorts were tested for statistical significance and 4 of 6 comparisons in the controlled cohort study (excluding the comparison with the general population). In the RCTs, only 4 out of 6 comparisons reported were tested for between group differences at the end of the trial. The table presents significance of results for number of comparisons made, organised by outcome. Conclusions: Large heterogeneity in type and reporting of studies, and outcomes hampers clear conclusions. Although trends towards beneficial effects on all work outcomes were shown, this effect proved often not significant either compared to the untreated group or to the baseline situation. Since the majority of studies were (extensions of) controlled trials, the generalizability of the effect of biologicals on work participation in daily practice should be further studied in larger population controlled studies or registers. References: Boonen A, van der Heijde D, Landewe R, et al. Work status and productivity costs due to ankylosing spondylitis: comparison of three European countries. Ann Rheum Dis. 2002 May;61(5):429-37. Disclosure of Interest: None Declared